(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
This study evaluated the effectiveness of a set of teaching procedures composed of videomodeling, written instruction and role-play with immediate feedback to teach caregivers to manage inappropriate behavior emitted by children with autism spectrum disorder (ASD). A multiple baseline design between two pairs of caregivers was implemented. The dependent variable was the accuracy of caregivers’ performance in the management of inappropriate behaviors, given by the percentage of procedural steps to manage inappropriate behaviors correctly implemented. The independent variable was the implementation of the set of procedures that taught the behaviors necessary to manage inappropriate behavior. The results show that the procedure used was effective to teach caregiver how to manage inappropriate behavior of children with ASD. The efficiency of the procedure was verified, since learning criteria was reached after only a few sessions, so that it can be considered a viable alternative to behavioral intervention focused on caregivers of children with ASD.